Molecular mechanisms of non-thermal atmospheric pressure plasma-induced cellular responses. (13th January 2021) - Hara, Hirokazu; Adachi, Tetsuo
Abstract: Non-thermal atmospheric pressure plasma (NTAPP) is an ionized gas that consists of charged particles, free radicals, and photons. The direct and indirect irradiation of cells with NTAPP has various biological effects, including wound healing and cell death. As NTAPP irradiation preferentially kills cancer cells, it is considered to be a promising application in cancer therapy. However, the reason why cancer cells are susceptible to NTAPP irradiation is not fully understood at present. Irradiation of liquids, such as culture medium, with NTAPP produces reactive oxygen species (ROS) and reactive nitrogen species (RNS) in the liquids. These reactive species have been demonstrated to play key roles in NTAPP-induced cellular responses. ROS/RNS-elicited modifications of biomolecules, such as protein thiol oxidation, cause inhibition of glycolysis and mitochondrial dysfunctions, leading to cell death associated with decreased energy production. We review current understanding of the mechanisms by which ROS/RNS generated by NTAPP elicit diverse cellular responses.